Kepuasan Petani Pada Lahan Usahatani Padi Sawah Bekas Peti di Desa Baru Kecamatan Pangkalan Jambu Kabupaten Merangin - Lubis, Arsyad; Zakiah, Zakiah; Kurniasih, Siti; Efran, Endy (Jurnal MeA (Media Agribisnis), 2024)
This research was carried out in Baru Village, Pangkalan Jambu District Merangin Regency with the aim of 1) Finding out the productivity of rice farming on reused land used by PETI, 2) Knowing farmers' satisfaction with rice farming on used PETI lowland and 3) Analyzing the relationship between productivity and farmer satisfaction. The activity of utilizing former PETI land by farmers in Baru Village, Pangkalan Jambu District is a breakthrough that must receive serious attention from all parties who feel they have an interest and concern for this effort to provide rice production as the main consumption material for the population. The total population in this study was 58 farmers, and all populations were used as samples. The research results show that the productivity of lowland rice farming on former PETI rice fields is 6.4 tons/ha, farmers are satisfied with lowland rice farming on former PETI fields. Chi Square Test analysis shows that there is a positive relationship between farmer satisfaction and the productivity of lowland rice farming on former PETI land. The calculated value of ðŒ2 = 6.71 > ðŒ2 table ( Î± =5 % db = 1) = 3.84 then it was decided to accept H1, meaning that the relationship between farmer satisfaction and the productivity of lowland rice farming on former PETI land is significant. Through the Contentency Test, the values C = 0.45 and Cmax = 0.707 are obtained, categorized as a strong relationship.categorized as a strong relationship.Kata Kunci ; Kepuasan, usahatani, sawah, PETI, Produktivitas.